Cognitive Distortions in Depressed Women: Trait, or State Dependent? - Sedat BATMAZ; Sibel KOCBIYIK (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: According to the cognitive theory developed by Beck, cognitive distortions are important mediators for the onset and maintenance of depressive disorders. It has not been researched if these cognitive distortions are more frequently encountered during the depressive episode, or if they are trait-like features. This study aims to investigate this. The hypothesis of the study is that cognitive distortions are state dependent. Method: Three groups of outpatients (n=178 patients in acute major depressive episode, n=168 depressive patients in remission, n=177 healthy controls) presenting to the psychiatry clinics of three different state hospitals were recruited for the study. The participants were diagnostically interviewed by the MINI according to the DSM-IV criteria. The participants were asked to complete the Cognitive Distortions Scale and the severity of their depression was measured by the Inventory for Depressive Symptomatology. Results: According to the cognitive distortion subscales, except for the self-blame subscale, the acute depressive group scored the highest. Also it was found that the cognitive distortions of the depressive populations, except for the self-blame related ones, statistically differed from the healthy controls. Self-blame related distortions were mood state dependent. Conclusion: The results have revealed that self-criticism, helplessness, hopelessness and preoccupation with danger related distortions had trait-like features, whereas self-blame related distortions were state dependent. This has clinical implications for the psychotherapeutic treatment of cognitive distortions in depression. Specifically, self-criticism related distortions should be managed during cognitive therapy for depression since the other subscales seem rather problematic. [JCBPR 2015; 4(3.000): 147-152]